Sobre a tradução de enérgeia e entelékheia em Física III, 1-3 - Ribeiro, Luis Felipe Bellintani (Laboratório OUSIA, 2019)
Regarding the issue of the motion on Aristotle, the conceptual pair « potency and act » is not only important, it practically exhausts the definition of motion, that, in the three initial chapters of book III of Physics, passage that we can call "Treaty of the Motion", is defined as "the act of the being in potency as such" (hetoû dynámei óntos entelékheia, hê(i) toioûton). In this definition the Greek word translated by "act" is entelékheia, but along the 161 lines of the "Treaty of the Motion" Aristotle employs 19 times the term entelékheiaand 21 times the term enérgeia, without making a clear distinction – like, by the way, also he doesn't make elsewhere – leading some translators to resignation in the face of an almost synonymy and to almost automatic translation of both Greek words by a single vernacular’s word, like “act”, “actuality”. How do we translate them anyway?